Technology leadership in teacher education : integrated solutions and experiences - Yamamoto, Junko, 1967- (Hershey, PA : Information Science Reference, 2010)
'This book presents international authors, who are teacher educators, and their best practices in their environments, discussing topics such as the online learning environment, multimedia learning tools, inter-institutional collaboration, assessment and accreditation, and the effective use of Web 2.0 in classrooms'--Provided by publisher.
Includes bibliographical references (p. 314-347) and index.
Keywords: Teachers -- Training of; Educational technology -- Study and teaching